Analisis Pengaruh Kreativitas Guru Terhadap Pengembangan Kreativitas Siswa dan Keterampilan Belajar Siswa Kelas 6 di SDN 106163 Bandar Klippa - Suyit Ratno; Saskhia Rahmadani; Erika Juliani Purba; Rika Silalahi; Anggi Brigita Saragih; Muhammad Gagah Prajaya; Stephani Fripania Sinurat (Lembag, 2024)
This study aims to analyze teachers' creativity in enhancing the development of students' IPAS learning skills at SDN 106163 Bandar Klippa through a qualitative descriptive interview method. Creative and innovative learning is a process that involves creativity and innovation. By engaging sixth-grade students from various backgrounds, this study focuses on how teachers foster students' creativity through creative learning methods. The learning process must be engaging and enjoyable so that students do not become bored. Many creative learning methods can be applied, such as cooperative learning, project-based learning, experiential learning, and problem-based learning. By using creative methods in learning, the learning environment becomes more enjoyable. Interview results show that students can enhance their creativity by creating works or media. However, they also experience difficulties in applying the concepts of media and their works, highlighting a lack of alignment between classroom learning and everyday experiences.